ORNAMEN MASJID MANTINGAN JEPARA JAWA TENGAH - Agus Setiawan (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
The research focuses on a study of how the ornaments on the Mantingan Mosque came to exist, what is the characteristic Islamic of the ornaments on the Mantingan Mosque, why the ornaments presents Hindu, Chinese, and local genius elements, and what is the symbolic meaning of the ornamental motifs it. The aim of the research was to discover and explain the existence of the ornaments, the facts behind the characteristic Islamic, why the ornaments presents Hindu, Chinese, and local genius elements, and the symbolic meaning of the ornamental motifs. The method used for the study was a qualitative research method. The location of the research was the site of the mosque and grave of Pangeran Hadiri and Ratu Kalinyamat in the village of Mantingan in Jepara. The data was collected through observation, interviews, a bibliographical study, and from documents and archives. The data was analysed using an interaction and interpretation analysis which was structured to cover a historical study, Islamic forms, symbolic meanings, and a conclusion. The results of the research showed that the existence of the ornaments are originated as decorations and teachings related to the figure of Pangeran Hadiri, Ratu Kalinyamat, and Sungging Badarduwung. The role of these three figures influenced the combination of artistic styles found in the ornaments of the Mantingan Mosque, namely Hindu, Chinese, and Islamic influences, together with the influence of a local genius. The characteristic Islamic of the ornaments developed through a process of acculturation in which art and cultural forms from outside were combined with art with an Islamic nuance. The symbolic meaning of the ornamental motifs on the Mantingan Mosque is the connection between the microcosm and macrocosm, depicted through motifs of plants, animals, imaginary creatures, interwoven patterns, buildings, and other inanimate objects.Keywords: ornaments, Mantingan Mosque, the symbolic meaning